CHANGES OF GLUCOSE IN SERUM BLOOD WHEY OF COWS DURING PREGNANCY AND THE POSTPARTUM PERIOD - Семерунчик, А. Д. (Scientific Progress & Innovations, 2013)
Biochemical parameters of blood serum of animals as an indicator of the body's metabolism may serve as markers of reproductive function disorders in animals. A dynamics of fluctuations in the level of glucose in the blood serum during pregnancy and postpartum period in cows of all ages is given. The increasing level of glucose relative to the upper limit of physiological serum of incalvers, due to activation of energy of metabolism of the mother is determined. Reduction of glucose in the blood serum in postnatal period to physiological limits indicates return the animal to the non-pregnant state.